The statistical thinking skill and adversity quotient of English pre-service teacher - Wahyu Hidayat; Sri Adi Widodo; Trisnendri Syahrizal (Institute of Advanced Engineering and Science, 2023)
Statistics is a branch of mathematical study in universities. Statistics courses are not too tricky to master for students in Mathematics education. In contrast, non-mathematics students, such as students of English education, own the paradigm that statistics is a complex subject since they have to apply formulas and substitute those formulas with numbers as a basic knowledge of general statistics course. There are a lot of studies on the statistical thinking skills of a pre-service teacher. However, statistical thinking skills influenced by the adversity quotient factor have not been widely studied. This study aimed to identify and examine the statistical thinking skills of pre-service English teachers based on the dimensions of adversity quotient and statistical thinking ability. This is a quantitative study with a sample of 314 students of English pre-service teachers who took statistics courses for language education and were selected by cluster random sampling technique at a university in Cimahi, West Java, Indonesia. The results showed that based on control, origin, ownership, and endurance positively influenced students’ thinking abilities. However, there is no positive effect between the latent variable of the reach dimension on the students’ statistical thinking ability. The students’ thinking skills tend to be classified at the quantitative level.